Does capital market drive corporate investment efficiency? Evidence from equity lending supply - Stephie Tsai, Hsin-Ju; Wu, Yuliang; Xu, Bin (Journal of Corporate Finance, 2021)
The increased equity lending supply (ELS) in the equity loan market, available for short sellers to borrow, exposes a firm to greater short selling threats. Considering short sellers' strong incentives to uncover firm-specific information and monitor managers, we hypothesize that short selling threats, proxied by ELS, enhance corporate investment efficiency. We find that ELS significantly reduces managerial tendencies to underinvest (overinvest) especially for firms prone to underinvest (overinvest). The effect of ELS on investment efficiency is stronger for firms with higher information asymmetry and weaker corporate governance, confirming short sellers' role in mitigating information and agency costs. However, short selling risk weakens the effect of ELS. Our evidence is robust to endogeneity checks and suggests that corporate investment can be driven by a particular capital market condition: the amount of lendable shares in the equity loan market.